Endolaserless Vitrectomy With Intravitreal Aflibercept Injection for Proliferative Diabetic Retinopathy-Related Vitreous Hemorrhage (LASER LESS TRIAL). (May 2018) - Marcus, Dennis M.; Singh, Harinderjit; Starnes, Davis C.; Walia, Harveen; Farooq, Amina; Frazier, Heather; Marcus, William B.; Lalane, Robert A.
Purpose: For proliferative diabetic retinopathy (PDR) eyes not requiring vitrectomy, Diabetic Retinopathy Clinical Research Protocol S and the CLARITY trial demonstrated better visual function and anatomical outcomes with less proliferative and diabetic macular edema consequences in the antivascular endothelial growth factor groups compared to the panretinal photocoagulation groups. Intravitreal aflibercept injection (IAI) may represent a useful therapy with vitrectomy for PDR-related vitreous hemorrhage (VH) as a viable alternative to intraoperative endolaser during vitrectomy. We will determine the safety and efficacy when aflibercept is used for PDR-related VH with endolaserless vitrectomy. Methods: Evaluation of endolaserless vitrectomy and 2 mg IAI for PDR-related VH. Eyes receive 1 preoperative and intraoperative IAI followed by randomization to a q8week group receiving 4 postoperative q4week IAI followed by q8week IAI or q16week group receiving 2 postoperative q4week IAI followed by q16week IAI. Main Outcome Measures: Herein, we present pooled safety and efficacy outcomes through 4 months. Results: Twenty-one of 24 eyes were randomized. Preoperative average visual acuity (VA) was 36 letters (20/200). At 4-month follow-up, 18 of 21 randomized eyes showed an average VA of 72 letters (20/40) with an average visual gain of 38 (range, 0-84 gain) letters. Average optical coherence tomography (OCT) central subfield thickness (CST) at 1-month postoperative follow-up was 311 µm. Average OCT CST at 4-month follow-up was 272 µm (average thinning of 38 µm). No significant short-term ocular or systemic adverse events were observed through 4 months. Conclusions: Endolaserless vitrectomy with IAI for PDR-related VH demonstrates short-term safety with significant VA improvement.